Views on working with information in a semi-digital society: Its possibility to develop as open innovation culture - Mikhail V. Vinichenko; Marina V. Rybakova; Oxana L. Chulanova; Sergey A. Barkov; Sergey A. Makushkin; Peter Karacsony (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
The transition from a semi-digital to digital society depends on the nature of work with information, and the speed and quality of digitalization largely depend on Generation Z. The purpose of the article is to identify and evaluate Gen Z's views in Russia and Slovakia on the search and assessment of information in a semi-digital society. The empirical research methods are a questionnaire survey, in-depth interviews, and a focus group. In the context of the COVID-19 pandemic, they were conducted remotely. The study reveals that the views of the Slovak and Russian Generation Z are similar in terms of searching and speeding up the acquisition of information and especially in the high assessment of their capabilities in information search and low confidence in advertising campaigns. The Slovak Gen Z is informationally mature and, at the same time, Internet-dependent. A difference in the perception of AI in Russian and Slovak Gen Z is identified. The results can be used to improve youth policies and provide information to society in the transition to fully digital life.
Keywords: 650; artificial intelligence; Generation Z (Gen Z); information; pandemic; semi-digital society